Response of rice hybrids to irrigation levels for yield, quality and water use during boro season in lower Gangetic plains of West Bengal - Mukherjee, Bishal; Ghosh, Mrityunjay; Banerjee, S; Jana, K (ORYZA-An International Journal of Rice, 2021)
The effect of irrigation regimes (irrigation at 1, 3 and 5 days interval) on four rice hybrids (6129 Gold, 6444 Gold, Tej Gold and DRH 775) was studied in split plot design during dry (boro) season of 2017 at Bidhan Chandra Krishi Viswavidyalaya, Nadia, West Bengal. Mean cultivar days to 50% flowering and maturity of hybrid rice were 99.1 and 125.9 days, respectively; while total summed GDD, HTU and PTU for entire life cycle were 1656°C day, 10410°C hour and 20311°C hour, respectively. Irrigation at 1 day interval resulted in highest grain yield (5.92 t ha-1), heat use efficiency (3.62 kg ha-1 °C day-1) and head rice recovery (58.2%), but lowest (3.08 kg ha-1 mm-1) water use efficiency (WUE). Among four hybrids, 6129 Gold yielded highest (5.88 t ha-1) with maximum WUE (4.44 kg ha-1 mm-1) and high-intermediate gelatinization temperature (score 3.0), that yield was 0.31, 0.42 and 0.51 t ha-1 greater over Tej Gold, DRH 775 and 6444 Gold, respectively. Irrigation regime could influence a few grain quality parameters viz. brown rice (73.8-75.6%), head rice recovery (53.3-58.2%) and alkali spreading score (score 3.2-4.1) in the investigation. Irrigation at 3 days interval might be adopted due to better WUE (5.02 kg ha-1 mm-1) with moderate grain yield (5.80 t ha-1) during boro season in lower gangetic plains of West Bengal.